2016
DOI: 10.1111/1467-9566.12482
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of dietary compliance among Italian children: disentangling the effect of social origins using Bourdieu's cultural capital theory

Abstract: Making use of Bourdieu's threefold conceptualisation of cultural capital, this paper examines and disentangles the association between social origins and children's food consumption. The aim of the work is twofold. Using data from the Multipurpose survey on daily life conducted by Istat (2009-2012), we first show that children's compliance with dietary advice is indeed influenced by their social origins, but more so in terms of familial cultural resources than economic ones. All types of cultural capital enhan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
31
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(36 citation statements)
references
References 45 publications
4
31
1
Order By: Relevance
“…The importance of childhood influences coincides with Oncini and Guetto's () findings on Italian children's food tastes, which showed that children's dietary compliance was mainly affected by their social origins. Similarly, Gross and Rosenberger () argue that even though the habitus is constantly changing, it does not change quickly or easily.…”
Section: Discussionsupporting
confidence: 84%
“…The importance of childhood influences coincides with Oncini and Guetto's () findings on Italian children's food tastes, which showed that children's dietary compliance was mainly affected by their social origins. Similarly, Gross and Rosenberger () argue that even though the habitus is constantly changing, it does not change quickly or easily.…”
Section: Discussionsupporting
confidence: 84%
“…Without further comprehensive research, conclusions about differences in SES offer insight into why inequalities exist in food and drink purchasing but no further awareness about links with positive or negative outcomes. Studies of younger children have, however, provided some insights (Oncini and Guetto, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Whether considering the culinary field (Johnston and Baumann, 2010), the relation between nutrition and health (Wright et al, 2015) or the procurement and provisioning of groceries (Oncini, 2019; Paddock, 2016), scholars have highlighted how meals can be used to mark boundaries and reproduce inequalities. Crucially, given the well-known association between children’s social origins and their patterns of food consumption (Oncini and Guetto, 2017) several authors have scrutinised the role of food in family relationships. Meals can be used to call into question and reconstruct family identities, trigger a mother’s moral accountability and carve a space for youngsters’ autonomy (Harman and Cappellini, 2015; Valentine, 1999; Wills et al, 2011).…”
Section: Children’s Food Between Home and Schoolmentioning
confidence: 99%
“…Building on the concept of habitus (Bourdieu, 1990; Reay, 1995), this article focuses on social class differences in children’s food knowledge and table manners in an Italian context. Despite a growing body of literature on children’s meals, dietary compliance and social stratification based on Bourdieu’s work (Oncini and Guetto, 2017; Wills et al, 2011), few studies consider the multifaceted ways in which social origins shape children’s relationship with food. This is somewhat surprising, as Bourdieu’s theorisation is markedly concerned with the reproduction of inequalities across generations and he is famously quoted as observing that ‘it is probably in tastes in food that one would find the strongest and most indelible mark of infant learning’ (Bourdieu, 1984: 79).…”
Section: Introductionmentioning
confidence: 99%